2015
DOI: 10.17265/1548-6583/2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital and Business Performance in Professional Football Clubs: Evidence From a Longitudinal Analysis

Abstract: This paper aims to explore the impact of intellectual capital efficiency (ICE) on firm performance in the context of professional football clubs. In particular, our aim is twofold: (1) to provide measures of ICE specifically tailored to professional football businesses; and (2) to empirically investigate whether some dimensions of ICE, namely,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In general, research has shown that human and structural capital are significant factors for market value. Therefore, we believe that footballers, considered intangible assets, are the ideal subjects for studies on intellectual capital, since their value takes into account their skills, the clubs they play for, and the relationship with supporters and teammates (Ricci et al, 2015).…”
Section: Theoretical Developments Regarding Intellectual Capital In F...mentioning
confidence: 99%
“…In general, research has shown that human and structural capital are significant factors for market value. Therefore, we believe that footballers, considered intangible assets, are the ideal subjects for studies on intellectual capital, since their value takes into account their skills, the clubs they play for, and the relationship with supporters and teammates (Ricci et al, 2015).…”
Section: Theoretical Developments Regarding Intellectual Capital In F...mentioning
confidence: 99%